The French foreign Legion / Wyatt Blassingame ; illustrated by Harper Johnson - Blassingame, Wyatt; Johnson, Harper (London : W. H. Allen, 1960)
Examines the lure of enlistment in the Legion and the types of individuals who join; describes the Legion's role in world military history and the men and battles that have enriched its reputation; and tells of the role of the Legion today
Keywords: France -- Armee -- Legion etrangere; France -- Army -- Foreign Legion; France -- History, Military